The white dwarf cooling sequence of 47 Tucanae - García Berro, E. (2014)
Context. 47 Tucanae is one of the most interesting, well-observed, and theoretically studied globular clusters. This allows us to determine the reliability of our understanding of white dwarf cooling sequences, to compare different methods of determining its age, and to assess other important characteristics, such as its star formation history. Aims. Here we present a population synthesis study of the cooling sequence of the globular cluster 47 Tucanae. In particular, we study the distribution of effective temperatures, the shape of the color-magnitude diagram, and the corresponding magnitude and color distributions. Methods. To do this, we used an up-to-date population synthesis code based on Monte Carlo techniques that incorporates the most recent and reliable cooling sequences and an accurate modeling of the observational biases. Results. Our theoretical models and the observed data agree well. Thus, our study disproves previous claims that there are still missing physics in the white dwarf cooling models at moderately high effective temperatures. We also derive the age of the cluster using the termination of the cooling sequence and obtain a good agreement with the age determinations made using the main-sequence turn-off. Finally, the star formation history of the cluster is compatible with that obtained using main-sequence stars, which predicts two distinct populations. Conclusions. We conclude that a correct modeling of the white dwarf population of globular clusters, used in combination with the number counts of main-sequence stars, provides a unique tool to model the properties of globular clusters.